Analysis of Provision of Green Open Space in Jambi City - Selamat; Dompak MT Napitupulu; Fuad Muchlis; Endi Adriansyah (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
Environment through the provision of parks and green open spaces (RTH), is carried out area and number of residents spread across the Jambi. urban areas is very necessary. Parks are needed to maintain land availability, as water catchment areas, which can play a role in helping water absorption, so that the supply of water in the ground (water saving) increases and reduces the potential for flooding, by reducing the amount of water runoff. This study used a quantitative descriptive method with research from the Jambi City Statistics Center (BPS). The research was carried out in the Administrative Region of Jambi City. The results of the analysis provision of public green space based on the area need for public green open space in Jambi City is 3,617.50 ha. The available public open space area is around 779.02 ha. Based on these results, there is a difference in the area of 2,838.48 ha, and the provision of public green open space based on population according to Minister of Public Works Regulation Number. 5 of 2008 it can be seen that the need for a park area in Jambi City is 1,243.70 ha. The available garden area is approximately 188,388.27 m2 or 18.84 ha. Based on these results, there is a difference in area shortage of 1,224.86 ha. Jambi City over the past 13 years (2020-2033) Some strategies Increasing the area of public open space in fulfilling intrinsic and extrinsic functions, socializing the availability of green space functions for life and the environment and Spatial planning that is equal to 20% for public open space from the total area of the city. The area of green open space in Jambi City is only 779.02 ha and is very far from the area of Jambi City which is ± 20,538 ha.